Modeling the distribution and intergenerational transmission of wealth - Smith, James D. (Studies in income and wealth, 1980)
This pioneering volume uses modern statistical and simulation techniques to explain the process of wealth transmission and the persistent problem of the unequal distribution of wealth. These papers reflect a shift from the traditional cross-sectional measurement to an intertemporal focus by attempting to model mathematically the actual process by which wealth is acquired and transmitted. There are many questions to be answered: What are the factors influencing saving? What is the role of mating? What decides ownership between spouses? How are rare assets distributed by divorce? What are the pa.